Diseño de un secador rotativo para 30 toneladas/h de arena, para la empresa Ecominesa S.A. (2019)
It was recognized that the company Ecominesa SA does not have a drying or moisture reduction system for the large volumes of sand they handle, due to this they have lost the opportunity to market their product to customers who require material for different applications such as glass, mortars for construction, castings, etc. Once the situation has been identified, different alternatives for the solution of the problem were proposed and the most appropriate design was chosen according to the large quantities of raw material to be processed, based on the information collected from various sources such as books, thesis, articles and websites. Once the best alternative for solving the problem has been selected, it was simulated using a finite element model (MEF). The manufacturing, assembly and assembly drawings were made. Then the manuals required by the machine were established, such as the operation, installation and maintenance, followed by the environmental impact of the development or manufacture of a machine of this type and to finish the financial evaluation to determine the profitability of the project.